2023
DOI: 10.3390/membranes13120897
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Receptors: Ex Vivo Functional Studies Enabling the Discovery of Hits and Pathways

Andrea Seldeslachts,
Steve Peigneur,
Jan Tytgat

Abstract: Histamine receptors (HRs) are G-protein-coupled receptors involved in diverse responses triggered by histamine release during inflammation or by encounters with venomous creatures. Four histamine receptors (H1R–H4R) have been cloned and extensively characterized. These receptors are distributed throughout the body and their activation is associated with clinical manifestations such as urticaria (H1R), gastric acid stimulation (H2R), regulation of neurotransmitters in neuronal diseases (H3R), and immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Regarding the structure, OS (Figure 1A) shares a similar structure with AEA (a partial agonist of CB1 receptors) and Org27569 (a positive allosteric modulator of CB1 receptors in binding, a negative allosteric modulator of CB1 receptors in function) (Figure S1), which indicates that it may act through CB receptors and, as seen in other studies that modulated CB receptors' function, affect behavior and memory [1][2][3]. Venoms can be seen as an untapped source of molecules that can be highly selective and potent ligands for a wide range of ion channels and receptors [27,28]. In the present study, we evaluated the effects of an endocannabinoid-like molecule found in cone snail venom.…”
Section: Introductionmentioning
confidence: 69%
“…Regarding the structure, OS (Figure 1A) shares a similar structure with AEA (a partial agonist of CB1 receptors) and Org27569 (a positive allosteric modulator of CB1 receptors in binding, a negative allosteric modulator of CB1 receptors in function) (Figure S1), which indicates that it may act through CB receptors and, as seen in other studies that modulated CB receptors' function, affect behavior and memory [1][2][3]. Venoms can be seen as an untapped source of molecules that can be highly selective and potent ligands for a wide range of ion channels and receptors [27,28]. In the present study, we evaluated the effects of an endocannabinoid-like molecule found in cone snail venom.…”
Section: Introductionmentioning
confidence: 69%
“…Its widespread use by millions of patients worldwide further supports its safety profile (Brennan et al, 2022). Histamine triggers the activation of protein kinase A, resulting in the (H+/K+) activation, which ultimately leads to elevated secretion of gastric acid (Seldeslachts et al, 2023). The H2R, which famotidine targets, extends beyond the stomach and is also present in other anatomical regions, including the pulmonary system (Mukherjee et al, 2021).…”
mentioning
confidence: 99%